PERANCANGAN ALAT BANTU PENILAIAN PENERIMAAN SUMBER DAYA MANUSIA DENGAN METODE SMART PADA CV. MONDAN - Silvia Sofyan (Sekolah Tinggi Manajemen Bisnis (STMB) MultiSmart, 2018)
Human Resources has a strategically important role in providing added value for an organization to achieve a competitive advantage. organizational progress can only be achieved with the support of qualified human resources. Banking companies such as cv mondan design an information system to improve the quality of human resources. Information system is a system that provides information for decision-making. With the human resources information system, issues related to operational activities such as recruitment and selection of employees, placement office, employee training and development and employee data management can be solved. Decision method adopted is a method SMART (Simple Multi-Attribute Rating Technique). Multi atribut decision-making technique is used to support decision-makers in choosing among several alternatives. Each criterion or alternatively they have more weight with a scale of 0 to 100 so that the results more accurate decisions. The system is designed with aplikasi.